PENERAPAN MODEL PEMBELAJARAN VISUALIZATION, AUDITORI, KINESTETIK DALAM PENINGKATAN HASIL BELAJAR SBdP TENTANG KARYA SENI KOLASE PADA SISWA KELAS IV SD NEGERI 2 KECILA TAHUN AJARAN 2020/2021. - Dyah Anis Nuresti; Tri saptuti Susiani; Wahyudi Wahyudi (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2022)
Abstract :The purpose of this study was to improve SBdP learning outcomes about collage art for fourth grade students with the Visualization Auditory Kinesthetic model. This research is a collaborative classroom action research carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection. The subjects of this study were grade IV students of the State Elementary School 2 Kecila for the 2020/2021 academic year, totaling 20 students. The data obtained come from teachers and students with observation, interview, and test data collection techniques. Data validity using triangulation technique with qualitative and quantitative analysis techniques. The results showed an increase in collage learning with the Visualization Auditory Kinesthetic learning model, the percentage of learning completeness in the first cycle was 52.50%, the second cycle was 70.00% and the third cycle was 87.50%. It can be concluded that the application of the Visualization Auditory Kinesthetic model can improve the learning of Cultural Arts and Crafts about the fourth grade collage of the State Elementary School 2 Kecila for the 2020/2021 Academic Year.  Abstrak :Tujuan penelitian ini adalah meningkatkan hasil belajar SBdP tentang karya seni kolase pada siswa kelas IV dengan model Visualization Auditory Kinesthetic.Penelitian ini merupakan penelitian tindakan kelas kolaboratif dilaksanakan dalam tiga siklus, setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas IV Sekolah Dasar  Negeri 2 Kecila Tahun Ajaran 2020/2021 yang berjumlah 20 siswa. Data yang diperoleh bersumber dari guru dan siswa dengan teknik pengumpulan data secara observasi, wawancara dan tes. Validitas data menggunakan teknik triangulasi dengan teknik analisis secara kualitatif dan kuantitatif. Hasil penelitian menunjukkan terjadi peningkatan pembelajaran kolase dengan model pembelajaran Visualization Auditory Kinesthetic, persentase ketuntasan belajar siklus I 52,50%, siklus II 70,00% dan pada siklus III 87,50%. Dapat disimpulkan bahwa penerapan model Visualization Auditory Kinesthetic dapat meningkatkan pembelajaran Seni Budaya dan Prakarya tentang kolase kelas IV Sekolah Dasar Negeri 2 Kecila Tahun  Ajaran 2020/2021.